KECERDASAN SOSIAL WARGA BELAJAR DI PKBM KAK SETO PEKANBARU - Siti Hardianti Simatupang; Daeng Ayub Natuna; Sumardi Sumardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the level of social intelligence of citizens studying at PKBM Kak Seto Pekanbaru. The formulation of the problem in this study is how high the social intelligence of citizens studying at PKBM Kak Seto Pekanbaru?. This study consists of 9 indicators, in accordance with opinions Howard Gardner. The population in this study were 60 people. This research sample uses techniques proporsionate stratified random samplingthat is, sampling is used when members of the population are not homogeneous consisting of homogeneous groups or proportional strata (Sugiyono, 2011:93).The data collection technique in this study was the questionnaire technique, which amounted to 100 statements. Data obtained from respondents totaling 20 people for the trial sample and 36 people for the study sample. After the questionnaire was tested, there were 5 invalid statements, and the researcher discarded invalid statements. Based on the average results of the mean value for the social intelligence variable of citizens learning at PKBM Kak Seto Pekanbaru is classified as high with Mean 3.80 and SD 0.80. The interpretation obtained for each indicator of social intelligence of citizens learning in PKBM Kak Seto Pekanbaru all classified as high, except linguistic intelligence. Even though the results are moderate one is still seenfrom the high average results. So, seen the most dominant of these 9 indicators is interpersonal intelligence. Key Words: Intelligence, Social Intelligence Learning Citizens